2017
DOI: 10.24212/2179-3565.2017v8i4p98-113
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Practices in Real Estate Housing in Ghana: Perception of Occupants

Abstract: Sustaianabilty has been and continues to be the one recurring topical issue the world over. Governments all over are turning serious attention towards the provision of sustainable urban housing for their urban populace. This they have realised holds the key to leading developmental growth for their economies.Building professionals are now confronted everywhere on green building and construction Ghana as a lower middle income country is grappled with a huge housing demand giving rise to a thriving real estate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…Chen et al (2014) also found that green transformational leadership had direct positive impact on green performance. We found that sustainable practice and managers' leadership relate with green transformation leadership which consistent with Pham & Kim (2019) and Danquah, J. A., Duah, D., & Marful, A.…”
Section: Discussionsupporting
confidence: 74%
“…Chen et al (2014) also found that green transformational leadership had direct positive impact on green performance. We found that sustainable practice and managers' leadership relate with green transformation leadership which consistent with Pham & Kim (2019) and Danquah, J. A., Duah, D., & Marful, A.…”
Section: Discussionsupporting
confidence: 74%